Anxiety and depressive symptoms in clinically isolated syndrome and multiple sclerosis - Carolina Fiorin Anhoque; Simone Cristina Aires Domingues; Thiago Carvalho; Antônio Lúcio Teixeira; Renan Barros Domingues (Arquivos de Neuro-Psiquiatria)
Depression and anxiety have been reported in patients with multiple sclerosis (MS) and in patients with clinically isolated syndrome (CIS). However, the precise mechanisms that lead to depressive and anxiety symptoms in these patients are still unclear. In this study we evaluated with the Beck Depression Inventory (BDI) and the Beck Anxiety Inventory (BAI) patients with MS and CIS and compared them to controls. We also correlated BDI and BAI scores with clinical parameters. Kruskall-Wallis followed by Dunn's Multiple Comparison Test, Chi-square and Spearman test were used. Patients with MS had higher depressive and anxiety scores than controls. The BDI and BAI scores of patients with CIS were not significantly different from controls. There was a positive correlation between BDI, BAI and EDSS. Our results corroborate the view that MS patients have higher depression and anxiety levels than control subjects. Anxiety and depressive symptoms also seem to progress according to the severity of the disease.